Effect of Glass Powder on the Compressive Strength and Drying Shrinkage Behavior of OPC- and LC3-50-Based Cementitious Composites of Various Strengths - Tehmina Ayub; Tariq Jamil; Ayesha Ayub; Asad-Ur-Rehman Khan; Eraj Mehmood; Muhammad Danyal Sheikh (Advances in Materials Science and Engineering)
This study assesses the compressive strength and drying shrinkage behavior of cement and LC3-50-based cementitious composites containing glass powder. A total of four, i.e., 20, 35, 50, and 60 MPa, strengths of cementitious composites were targeted by varying the mix composition and water-to-cement ratios. In all four composite mix types, locally available glass powder was used as 0, 5, 10, and 15% added as a partial replacement of cement and LC3-50. The novelty of this research is the addition of waste glass powder as an alternative to silica fume, especially in a high-strength composite (including 50 and 60 MPa). The aim was to investigate the efficiency of waste glass powder in providing eco-friendly composites. The compressive strength was determined following ASTM C 109 standard and the drying shrinkage test followed ASTM C 157 standard. The results of compressive strength in the enhancement using up to 10% waste glass powder are beneficial in enhancing strength and reducing drying shrinkage. Furthermore, the use of LC3-50 initially reduced compressive strength up to 14 days while increased at 28 days compared to OPC. Contrariwise, the initial drying shrinkage was higher in LC3-50 specimens and lower at later ages compared to OPC. A detailed investigation of existing shrinkage models for mortar/composite is assessed, and limitations are also discussed.